NEXUS Gains: Realizing Multiple Benefits Across Water, Energy, Food and Ecosystems (Forests, Biodiversity) - Ringler, Claudia (2022)
Claudia Ringler, IFPRI and co-lead NEXUS Gains Islamabad October 24, 2022